2018
DOI: 10.1371/journal.pone.0206795
|View full text |Cite
|
Sign up to set email alerts
|

Rates and determinants of neonatal mortality in two rural sub-districts of Sylhet, Bangladesh

Abstract: IntroductionReducing neonatal mortality rate (NMR) is a challenge in many low- and middle-income countries including Bangladesh. In 2014, the estimated NMR in this country was 28 per 1,000 live births. This rate is higher in rural regions compared to the national average. Currently, Sylhet Division has the highest NMR in Bangladesh. Investigating rates and determinants of neonatal mortality in rural regions of this high-risk division is particularly important to implement evidence-based programs. This study ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

10
30
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(40 citation statements)
references
References 44 publications
(73 reference statements)
10
30
0
Order By: Relevance
“…Prior studies that assessed socio-demographic factors for NNM, have not established a signi cant association between NNM and maternal education [7,15,18,26,41]. However, a universal association between maternal education and neonatal mortality, especially in the low-income countries, has been demonstrated [39,59,61,62], and supports current study's ndings. In addition, educated mothers are more likely to come from a higher socioeconomic status [59], have a better knowledge of healthy behaviours, have a more informed approach to self-care, make better health-related choices, and utilize the healthcare system appropriately [31,63].…”
Section: Discussionsupporting
confidence: 84%
See 3 more Smart Citations
“…Prior studies that assessed socio-demographic factors for NNM, have not established a signi cant association between NNM and maternal education [7,15,18,26,41]. However, a universal association between maternal education and neonatal mortality, especially in the low-income countries, has been demonstrated [39,59,61,62], and supports current study's ndings. In addition, educated mothers are more likely to come from a higher socioeconomic status [59], have a better knowledge of healthy behaviours, have a more informed approach to self-care, make better health-related choices, and utilize the healthcare system appropriately [31,63].…”
Section: Discussionsupporting
confidence: 84%
“…Advanced maternal age [15] and under age (<18 years) [27] was signi cantly associated with NNM. Similarly, signi cant association has been reported between advanced maternal age [38,39,69] or younger age (< 20 years) [57,58,62], and adverse neonatal outcomes. Secondary analysis of the WHO multi-country survey on maternal and newborn health ndings showed that advanced maternal age signi cantly increased the risk of stillbirths and perinatal mortalities [77].…”
Section: Discussionmentioning
confidence: 83%
See 2 more Smart Citations
“…This elucidates the likelihood of NNM affecting nulliparous women [32,38]. Prior studies have shown that first-born infants are at higher risk of neonatal mortality than the second-or thirdborn infants [43,45]. However, in some studies, parity was not shown to have an association with neonatal mortality [46].…”
Section: Discussionmentioning
confidence: 99%